The OXT rs6133010 variant modulates susceptibility to psychiatric symptoms during withdrawal in patients with alcohol dependence - Guanghui Shen; Wei Wang; Yuyu Wu; Xinguang Luo; Kexin Wang; Yu-Hsin Chen; Yimin Kang; Yanlong Liu; Fan Wang; Li Chen (BMC Psychiatry)
Abstract Background Alcohol dependence (AD) confers susceptibility to distressing withdrawal symptoms that often lead to relapse. While neuroadaptation during withdrawal influences symptoms, the genetic factors behind it have not been thoroughly investigated. We utilized propensity score matching and investigated connections between AD, OXT rs6133010, and withdrawal symptoms to address confounding variables. By elucidating the OXT rs6133010-AD interaction, we aim to gain insights into alcohol withdrawal variability and contribute to personalized treatment approaches. Methods A cross-sectional study design was employed involving a total of 389 AD patients and 184 healthy controls who were genotyped for the OXT rs6133010 polymorphism. Psychiatric symptoms were evaluated using standardized scales during early withdrawal. Propensity score matching mitigated age and education differences. Results A two-way ANOVA demonstrated a significant AD x OXT rs6133010 interaction effect on hostility and anxiety. Further analysis revealed that the regulatory impact of OXT rs6133010 was exclusively in AD patients. Specifically, AD patients with the AA homozygote showed robust protection against hostility and anxiety. Path analysis unveiled the underlying mechanism of OXT symptom regulation. Conclusion This study presents novel evidence that OXT rs6133010 specifically modulates psychiatric symptoms in AD. The G allele may heighten hostility and anxiety vulnerability during alcohol withdrawal. These findings emphasize considering environmental factors when studying and utilizing oxytocin therapeutically. Additionally, OXT may not directly act as an anxiolytic but instead regulates anxiety by modulating hostility.